Therapy-induced senescence of glioblastoma cells is determined by the p21CIP1-CDK1/2 axis and does not require activation of DREAM - Christian Schwarzenbach; Justus Rinke; Juliana B. Vilar; Jason Sallbach; Larissa Tatsch; Ariane Schmidt; Anna Schöneis; Birgit Rasenberger; Bernd Kaina; Maja T. Tomicic; Markus Christmann (Cell Death and Disease)
Abstract Therapy-induced senescence (TIS) is a major challenge in cancer therapy as senescent cancer cells provoke local and systemic inflammation and might be the cause of recurrences. Elucidation of pathways leading to TIS is of utmost importance for establishing strategies to counteract this. Previously we have shown that temozolomide (TMZ), an alkylating drug used forefront in glioma therapy, causes majorly cellular senescence, which is triggered by the primary damage O6-methylguanine, activating the mismatch repair dependent ATR/ATM-CHK1/CHK2-p53 damage response pathway. The downstream pathways leading to TIS remained to be explored. Here, we show that TMZ-induced TIS in glioma cells does not require activation of the DREAM complex, but is bound on a G2-specific response. We show that the CDK inhibitor p21CIP1 does not interact with CDK4, but with CDK1 and CDK2 causing abrogation of the B-Myb and FOXM1-signaling pathway and subsequently arrest of cells in the G2-phase. The induced G2-arrest is incomplete as DNA synthesis can be resumed leading to endoreduplications. This process, which is inhibited by the CDK4-blocking drug palbociclib, is preceded by reactivation of the G1/S-specific E2F1-signaling pathway due to lack of functional DREAM activation. These findings provide an explanation for the polyploidization and giant cell phenotype of anticancer drug-induced senescent cells. Incomplete DREAM activation may also explain the observation that downregulation of DNA repair is a transient phenomenon, which goes along with the entrance of cells into the senescent state.